2008
DOI: 10.1108/10595420810874655
|View full text |Cite
|
Sign up to set email alerts
|

Managerial decision making and competitiveness: the case of Hungary

Abstract: Purpose -The purpose of this paper is to explore three key aspects of managerial decision making, namely managerial skills and attitudes, information and performance measurement supporting decision making, and companies' approaches to the management of relationship with their stakeholders. Design/methodology/approach After giving a hroad view of the management practice of the sample, the paper analyzes the differences (by company size, dominant ownership, and performance) of companies according to the routines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Secondly, a large number of authors (Čadež 2002;Szychta 2002;Haldma/Lääts 2002;Pärl 2006;Wagner et al 2007;Zoltay Paprika et al 2008) reported the lack of appropriate management accounting knowledge as a factor holding back the development and use of contemporary performance measurement systems.…”
Section: Overall Discussion On Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, a large number of authors (Čadež 2002;Szychta 2002;Haldma/Lääts 2002;Pärl 2006;Wagner et al 2007;Zoltay Paprika et al 2008) reported the lack of appropriate management accounting knowledge as a factor holding back the development and use of contemporary performance measurement systems.…”
Section: Overall Discussion On Future Researchmentioning
confidence: 99%
“…Thirdly, empirical research still fails to build on prior studies to increase the understanding of the topic. Only a couple of studies use the longitudinal approach or build on prior research (Epstein et al 2004;Rejc Buhovac/Slapničar 2007;Bodnár et al 2007;Zoltay Paprika et al 2008).…”
Section: Overall Discussion On Future Researchmentioning
confidence: 99%
See 1 more Smart Citation